America's covert border war : the untold story of the nation's battle to prevent jihadist infiltration - Bensman, Todd (Bombardier Books, 2021)
This thirteen-year work of journalism finally settles one of the nation's most controversial and politically powerful ideas about the American southern border: that Islamic jihadists might infiltrate it and commit terrorist acts. Perhaps no other idea about the border has sown more conflict, claims, counterclaims, rebuttals, and false narratives on all sides.